2002
DOI: 10.2337/diabetes.51.2007.s478
|View full text |Cite
|
Sign up to set email alerts
|

Production and Characterization of Reg Knockout Mice

Abstract: Reg (regenerating gene) was isolated as a gene specifically expressed in regenerating islets. We have demonstrated in vitro and in vivo that the exogenous addition of rat and human Reg gene products, Reg/REG proteins, induced ␤-cell replication via the Reg receptor and thereby ameliorated experimental diabetes. In the present study, we produced Reg knockout mice by homologous recombination. The Reg gene disruption resulted in a null mutation. Knockout mice developed normally. Islets from the Reg knockout mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
97
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(102 citation statements)
references
References 33 publications
5
97
0
Order By: Relevance
“…Although Reg proteins are known to function as ␤ cell trophic factors, it has also been shown that Reg2 in the pancreas can function as an autoantigen and the target of an islet-destructive process (28,29). However, when Reg was specifically expressed as a transgene in the pancreas of NOD mice, the onset of diabetes was significantly delayed (23). Although the molecular mechanism leading to up-regulated Reg expression in the Il21r-KO remains to be determined, it is thus possible that the augmented Reg gene expression contributes to the protective effect from diabetes observed in the Il21r-KO NOD mice.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Although Reg proteins are known to function as ␤ cell trophic factors, it has also been shown that Reg2 in the pancreas can function as an autoantigen and the target of an islet-destructive process (28,29). However, when Reg was specifically expressed as a transgene in the pancreas of NOD mice, the onset of diabetes was significantly delayed (23). Although the molecular mechanism leading to up-regulated Reg expression in the Il21r-KO remains to be determined, it is thus possible that the augmented Reg gene expression contributes to the protective effect from diabetes observed in the Il21r-KO NOD mice.…”
Section: Discussionmentioning
confidence: 96%
“…Regenerating gene (Reg) was identified as a gene that is upregulated in regenerating pancreatic ␤ islet cells (22). Whereas deletion of the Reg2 gene led to decreased proliferation of the pancreatic ␤ islet cells, NOD mice carrying a Reg2 transgene specifically expressed in the pancreas displayed a significant delay in the onset of diabetes (23). We therefore examined the expression of two members of this family of proteins, Reg2 and PAP, in the pancreas of WT and Il21r-KO mice either on the NOD or on the C57BL/6 background.…”
Section: Normal T Cell Populations and Cytokine Production In Nod/il2mentioning
confidence: 99%
“…Generation of the Reg I-knockout mice is described in our previous report (Unno et al, 2002). Reg I-knockout mice (Reg À/À ) were bred with ICR wild-type mice (Nihon Clea, Tokyo, Japan), generating Reg þ /À mice.…”
Section: Animalsmentioning
confidence: 99%
“…Regenerating islet (Reg) proteins have been identifi ed in various types of regenerating tissues [10,11,51,52] and cancer cells [ 13,14,16 ] and the expression patterns of Reg genes have been under intense scrutiny. To date, however, there clearly demonstrate an increase in Reg1 expression in mouse MIN6 insulinoma β-cells treated with gastrin.…”
Section: Discussionmentioning
confidence: 99%